Implementation of Federal Constituency Projects and the Development of Infrastructure in Kogi State (2012-2022) - Adekeye, Joseph Adeshola; Ofoma, Chinedu Valentine (JPAS (Journal of Public Administration Studies), 2023)
This paper assesses the impact of the implementation of federal constituency projects on the development of infrastructure in Kogi State from 2012 to 2022. The main objective of the study was to determine the contributions of federal constituency projects to the development of economic and social infrastructure in each Senatorial District of Kogi State. Methodologically, a descriptive survey was adopted for the purpose of data collection, analysis and interpretation. Out of 321 questionnaire administered to selected respondents in the 3 Senatorial Districts of Kogi State, 302 were completed and returned appropriately. Data collected were analyzed using the Statistical Package for Social Sciences (SPSS) as a tool for data presentation and hypotheses test. Also, the study made use of secondary data sourced from Tracka, journal articles, empirical studies, newspaper publications among others. The findings of the study reveal that the implementation of federal constituency projects has significantly impacted on the development of economic and social infrastructure in some communities in Kogi State while others are yet to benefit. However, the level of constituency projects implementation in Kogi State from 2012-2022 is a far cry from annual budgetary allocation and specifications. This paper therefore recommends that members of each respective constituency in Kogi state must be carried along from the period of project initiation to its completion so as to hold all relevant stakeholders accountable for any lapses. Likewise, the press and Civil Society Organizations are to ensure that legislative oversights are properly carried out in order to ascertain whether project implementation is in line with approved budget.